Anxiety Disorder among Older Adults with Visual Impairment in Ekiti, Nigeria: Implications for the Potential Opportunity to Mitigate the Impact of the Disability and Prevent Psychological Harm - Aina, Felix Olukayode; Ajayi, Iyiade Adeseye; Omotoye, Joseph Olusola; Agbesanwa, Tosin Anthony; Dada, Mobolaji Usman; Fadare, Joseph Olusesan; Ajite, Olumide Kayode; Prajjwal, Priyadarshi (Folia Medica Indonesiana, 2023)
Highlights: Anxiety is an important morbidity among visually impaired older adults. There is potential for stakeholders to specifically channel their interventions towards particular IVI domains in order to reduce anxiety prevalence. Abstract: Visual impairment is a significant morbidity among adults globally. It has negative impacts on work force participation and productivity, as and well as higher depression and anxiety disorder rates. In the case of older adults, vision impairment can contribute to social isolation and a greater likelihood of early entry into nursing or care homes. This hospital-based, cross-sectional study was designed to determine anxiety disorder's prevalence among the study population and which Impact of Visual Impairment (IVI) domain is most correlated with anxiety disorder. The study was carried out at the Ophthalmology Clinic of the Ekiti State University Teaching Hospital, Ado Ekiti, Nigera. Questionnaires were used to collect information from 115 respondents. Information sought included sociodemographic information, anxiety status, and visual impairment's impact on daily functions. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety disorder, while the IVI scale was used to assess the impact of visual impairment. The IVI scale is an instrument used for determining the impact of visual impairment under three domains: (reading and accessing information, mobility and independence, and emotional well-being). Anxiety disorder was detected in 10.4% of all the respondents, and the IVI's mobility and independence domain of IVI was most strongly correlated with anxiety disorder.